Wilbur Smith´s Egyptian novels - Urbánková Martina (Univerzita Pardubice, 2011)
This diploma thesis deals with Wilbur Smith´s tetralogy of "Egyptian" novels and through the consequent analysis tries to reveal the main thematic domains on which the whole series is based on. The preface discusses the theoretical terminology concerning genres such as adventure novel, historical novel and their overlapping and resulting in the genre historical adventure novel for Egyptian series belong into this genre. Then,the biography of the famous author Wilbur Smith with his labelling as a postcolonial writer follows. Thereafter, the principal focus of this work is on the analysis where the main revealed thematic domains regarding historical authenticity, sexuality and violence in terms of incidence and significance. Finally, the complexity of translation of Egyptian novels is dealt with where the main focus is on Smith´s style of writing concerning lexical as well as syntactic features. All these aspects are compared with Czech translations and potential problems discussed. As a matter of the fact that two different translators participated on translating the tetralogy, the complexity of this issue with consequent conclusions are presented too.
"Egyptské romány" Wilbura Smithe
Keywords: historické romány; dobrodružné romány; post-kolonialismus; překlady; násilí; historical fictions; adventure novels; post-colonialism; translation; violence; Smith, Wilbur